Efisiensi Produksi Bawang Prei (Allium Ampeloprasum) Di Pertanian Organik (Porkab) Desa Suberejo Kecamatan Batu Kota Batu - Wahid, Moh.; Pudjiastuti, Agnes Quartina; Khoirunnisa, Ninin (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
This study aims to analyze the production factors of leek farming, analyze the efficiency of leek farming in PORKAB. Respondents amounted to 30 people with saturated sampling technique. To determine the effect of the use of production factors on leek farming using Cobb-Douglas analysis, and to determine the level of efficiency in leek farming using three parts of production inputs technically, allocatively and economically. The results of this study indicate that the factors that affect production in leek farming, namely vegetable pesticides, have a significant effect, while land area, labor, seeds, and manure have no significant effect on leek production. Technically, the area of land, seeds, manure and vegetable pesticides in leek farming is not technically efficient while the workforce is technically inefficient. The total value of technical efficiency, which is 1.017, is greater than 1, meaning that the proportion of additional production factors will result in greater production. Allocatively, labor and manure have an allocative efficiency value greater than 1, meaning that leek farming is not allocatively efficient. In the area of land, seeds and vegetable pesticides are smaller than 1, meaning that leek farming is not allocatively efficient. While economically on land area, seeds and vegetable pesticides are not economically efficient, while labor and manure are not economically efficient.Keywords: Efficiency, Prey Onion,Â Production.